2018
DOI: 10.1111/1747-0080.12456
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Food Frequency Questionnaire for Brazilian athletes

Abstract: Using a multiple regression analysis we developed a 59-food item questionnaire, which includes culturally specific food items and may represent an important dietary tool to analyse athletic populations. Reproducibility and validity of this FFQ will be verified in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Information on food intake from two working days and one non-working day was obtained. The aim of the three-day dietary recall is to provide individual variation in food and dietary intakes [ 38 ]. In the dietary recall, the respondents were asked about the foods they eat and how the foods were prepared, for example whether it includes frying, boiling, roasting, steaming, or other methods.…”
Section: Methodsmentioning
confidence: 99%
“…Information on food intake from two working days and one non-working day was obtained. The aim of the three-day dietary recall is to provide individual variation in food and dietary intakes [ 38 ]. In the dietary recall, the respondents were asked about the foods they eat and how the foods were prepared, for example whether it includes frying, boiling, roasting, steaming, or other methods.…”
Section: Methodsmentioning
confidence: 99%
“…With the rise in the consumption of plant‐based diets, Waterplus et al use a plant‐based diet index that discerns between healthy and unhealthy sources to monitor changes over a 10‐year period and the impact on blood lipids . Finally, Godois et al look at a particularly time‐poor population—athletes—and describe the use of multi‐pass 24‐hour food recalls to develop a list of foods for an FFQ to explain nutrient variability in Brazilian athletes …”
Section: Dietitian‐nutritionists: Practising the Art And Science Of Nmentioning
confidence: 99%
“…The food frequency questionnaire (FFQ) is usually used to evaluate long-term dietary intake [12][13][14][15][16]. Studies have shown that the FFQ is the most feasible and cost-effective tool compared to other dietary assessment methods [17].…”
Section: Introductionmentioning
confidence: 99%